Approaches to optimize patient and family engagement in hospital planning and improvement: Qualitative interviews. (24th March 2021) - Anderson, Natalie N.; Baker, G. Ross; Moody, Lesley; Scane, Kerseri; Urquhart, Robin; Wodchis, Walter P.; Gagliardi, Anna R.
Abstract: Background: Patient engagement (PE) in health‐care planning and improvement is a growing practice. We lack evidence‐based guidance for PE, particularly in hospital settings. This study explored how to optimize PE in hospitals. Methods: This study was based on qualitative interviews with individuals in various roles at hospitals with high PE capacity. We asked how patients were engaged, rationale for approaches chosen and solutions for key challenges. We identified themes using content analysis. Results: Participants included 40 patient/family advisors, PE managers, clinicians and executives from 9 hospitals (2 < 100 beds, 4 100 + beds, 3 teaching). Hospitals most frequently employed collaboration (standing committees, project teams), followed by blended approaches (collaboration + consultation), and then consultation (surveys, interviews). Those using collaboration emphasized integrating perspectives into decisions; those using consultation emphasized capturing diverse perspectives. Strategies to support engagement included engaging diverse patients, prioritizing what benefits many, matching patients to projects, training patients and health‐care workers, involving a critical volume of patients, requiring at least one patient for quorum, asking involved patients to review outputs, linking PE with the Board of Directors and championing PE by managers, staff and committee/team chairs. Conclusion: This research generated insight on concrete approaches and strategies that hospitals can use to optimize PE for planning and improvement. On‐going research is needed to understand how to recruit diverse patients and best balance blended consultation/collaboration approaches. Patient or public contribution: Three patient research partners with hospital PE experience informed study objectives and interview questions.